Evaluation of outcomes in elderly patients diagnosed with colorectal cancer - Lawrence, Neil; Griffiths, Joshua; Chapple, Keith (International Surgery Journal, 2018)
Background: Colorectal cancer in the elderly carries a high morbidity and mortality. The National Bowel Cancer Audit Programme is a high-quality audit incorporating all UK colorectal cancer patients. Author analysed this database to investigate the local outcomes for this high-risk group. Methods: Data (mode of presentation, presence of metastatic disease, treatment surgery, colonic stent or conservative and WHO performance status) was collected on all patients aged 85 years or over diagnosed with colorectal cancer at a large tertiary referral centre over a 5-year period. Ninety day and 2 year-mortality was obtained for all patients. Results: Ninety patients (45 male, 45 female, median age 88.9 range 85.0-97.9 years) were included (47 emergency presentation, 43 elective presentation). A 18 of 47 patients underwent emergency surgery. A 90-day and 2-year mortality in this group was 17% and 69% respectively. 29 of 47 patients presenting as an emergency had non-operative treatment (2-year mortality 87%). Two years mortality for patients undergoing emergency surgery was 100% if aged above 90 years or if distant metastases were present. Eleven of 43 patients presenting electively underwent surgery. 90-day and 2-year mortality for this group was 18% and 0% respectively. Two years mortality for those presenting electively and undergoing non-operative treatment was 62%. Conclusions: Decision making must be very carefully considered in patients aged over 85 years as the presence of metastases, poor WHO performance status or age over 90 carries with it a significant risk of mortality at both 90 days and 2 years following diagnosis.